Evaluation of professional competencies of Kazakhstan university students - Yelena Aleksandrovna Gripp, Gulnur Oralbaevna Issakova, Maral Duiseneevna Yessekeshova,; Elmira Dzhumabaevna Alimkulova, Kulyan Zhagiparovna Ibrayeva, (Opción, 2019)
The goal of this research is to create a methodological approach to evaluating the level of professional competencies of graduates as a factor improving employment prospects via canonical analysis. In result, all professional competencies of graduates from Kazakhstan universities are currently at a low level. The low level of professional training competencies is primarily due to the lack of practical job skills. In conclusion, the main factors for successful employment of university graduates at the labor market in the Republic of Kazakhstan are professional skills in the relevant field, as well as the competencies of professional socialization and professional mobility.